Four-dimensional Fano toric complete intersections - Coates, Tom; Kasprzyk, Alexander M.; Prince, Thomas (Royal Society, 2015)
We find at least 527 new four-dimensional Fano manifolds, each of which is a complete intersection in a smooth toric Fano manifold.